Temperature sensitivity of biomass‐specific microbial exo‐enzyme activities and CO2 efflux is resistant to change across short‐ and long‐term timescales. (20th March 2019) - Min, Kyungjin; Buckeridge, Kate; Ziegler, Susan E.; Edwards, Kate A.; Bagchi, Samik; Billings, Sharon A.
Abstract: Accurate representation of temperature sensitivity ( Q 10 ) of soil microbial activity across time is critical for projecting soil CO2 efflux. As microorganisms mediate soil carbon (C) loss via exo‐enzyme activity and respiration, we explore temperature sensitivities of microbial exo‐enzyme activity and respiratory CO2 loss across time and assess mechanisms associated with these potential changes in microbial temperature responses. We collected soils along a latitudinal boreal forest transect with different temperature regimes (long‐term timescale) and exposed these soils to laboratory temperature manipulations at 5, 15, and 25°C for 84 days (short‐term timescale). We quantified temperature sensitivity of microbial activity per g soil and per g microbial biomass at days 9, 34, 55, and 84, and determined bacterial and fungal community structure before the incubation and at days 9 and 84. All biomass‐specific rates exhibited temperature sensitivities resistant to change across short‐ and long‐term timescales (mean Q 10  = 2.77 ± 0.25, 2.63 ± 0.26, 1.78 ± 0.26, 2.27 ± 0.25, 3.28 ± 0.44, 2.89 ± 0.55 for β‐glucosidase, N ‐acetyl‐β‐d ‐glucosaminidase, leucine amino peptidase, acid phosphatase, cellobiohydrolase, and CO2 efflux, respectively). In contrast, temperature sensitivity of soil mass‐specific rates exhibited either resilience (the Q 10 value changed and returned to the original value over time) or resistance to change. Regardless of the microbial flux responses, bacterial and fungal community structure was susceptible to change with temperature, significantly differing with short‐ and long‐term exposure to different temperature regimes. Our results highlight that temperature responses of microbial resource allocation to exo‐enzyme production and associated respiratory CO2 loss per unit biomass can remain invariant across time, and thus, that vulnerability of soil organic C stocks to rising temperatures may persist in the long term. Furthermore, resistant temperature sensitivities of biomass‐specific rates in spite of different community structures imply decoupling of community constituents and the temperature responses of soil microbial activities. Abstract : We investigated how microbial temperature responses vary across timescales and what mechanisms drive such temporal patterns. We demonstrated that biomass‐specific rates of exo‐enzyme activities and CO2 effluxes exhibited resistant temperature sensitivities across time, in spite of changing microbial community composition with exposure to short‐ and long‐term exposure to different temperature regimes. Those expressed as soil mass‐specific rates exhibited resistance or resilience depending on the flux rate assessed.